THE EFFECTS OF LANGUAGE LEARNING STRATEGIES (LLS) ON ENGLISH LANGUAGE PROFICIENCY - Mehwish Riaz; Iram Ashraf; Amna Alam, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This article contains a deeper analysis of the language learning strategies and their effect on the language proficiency. Researchers, in past two three decades, have done a lot of research on the learning strategies to show their effectiveness during the learning process but still couldn’t come a definite conclusion due to the variable results, nature and fuzziness of the topic. Views/opinions of some researchers have been included in the literature review segment to give a clear idea. Students were chosen from 1st professional year of Economics department of NUML University where Economics-English language course was specifically designed to increase their English language skills in Economics domain. Few tests were carried out and results are given in the section four of this article. There is a detailed discussion in section five of this article to show a positive/negative connection between language learning strategies and the proficiency outcome. Different strategies used by the students show different results which leaves us with no definite conclusion. The hypothesis of the article is challenged with the results and a possible conclusion is added in the last part of the study.